2018
DOI: 10.1590/0103-8478cr20170761
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the genotypic performance of carioca beans through mixed models

Abstract: Using genotypes adapted to different regions is one of the main ways to increase Brazilian bean yield. The aim of the present study was to assess the genotypic performance of Carioca beans through mixed models. Fourteen Carioca bean genotypes were assessed in four locations in Pernambuco State (Arcoverde, Caruaru, Belém de São Francisco and São João counties) in 2015. The experiments followed a completely randomized block design, with three repetitions. Genetic parameters were estimated according to the REML/B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
5
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 9 publications
3
5
0
1
Order By: Relevance
“…For the 2016-2017 black bean and the 2018-2019 purple bean genotypes, on the other hand, due to the low correspondence between the observed phenotypic and predicted genotypic values, the selection of superior genotypes is possible, but more difficult. Similar findings were reported by Santos et al (2018), who estimated accuracy at 75.91 and 15.72 % for black and carioca bean genotypes, respectively, under the same conditions as in the present study.…”
Section: Effectsupporting
confidence: 92%
See 1 more Smart Citation
“…For the 2016-2017 black bean and the 2018-2019 purple bean genotypes, on the other hand, due to the low correspondence between the observed phenotypic and predicted genotypic values, the selection of superior genotypes is possible, but more difficult. Similar findings were reported by Santos et al (2018), who estimated accuracy at 75.91 and 15.72 % for black and carioca bean genotypes, respectively, under the same conditions as in the present study.…”
Section: Effectsupporting
confidence: 92%
“…Under these conditions, the selection of superior genotypes is possible, although more costly. Cruz et al (2018) and Souza et al (2018) observed similar results, estimating values of low magnitude and lower than the experimental coefficient of variation for green bean and black bean genotypes, respectively.…”
Section: Resultssupporting
confidence: 54%
“…In this context, genotypes with higher yield in an environment tend to exhibit distinct performances in several environments, in addition to unpredictability and low adaptation to environmental variations. Consequently, low values of genotypic correlation were obtained in the different environments, which caused changes in the order of the genotypes selected (SOUZA et al, 2018;SANTOS et al, 2019).…”
Section: Resultsmentioning
confidence: 99%
“…It also generates results in the unit itself or the scale of the trait evaluated, which may be directly interpreted as breeding values that are not allowed by other methods. This model also allows additional inferences, such as the selection of specific genotypes for each environment; selection of stable genotypes (high predictability) in different environments and years; selection of genotypes (high adaptability) responsive (high adaptability) to the improvement of the environment; and simultaneous selection for yield, stability, and adaptability (CARVALHO et al, 2016;GONÇALVES et al, 2014;SANTOS et al, 2017;SANTOS et al, 2018;SANTOS et al, 2019;SOUZA et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…In the summaries of the joint analysis of variance of the trials, significant differences were observed by the F test (P < 0.01) between the sources of variation corresponding to genotypes, environments and G × E interaction, indicating genetic variability between genotypes, heterogeneity in the environmental conditions in which the experiments were conducted and that the genotypes present different responses to different environments (Table 3). The G × E interaction interferes in the stage of genotype selection and subsequent indication of cultivars, since the observed phenotype may not be befitting with the real potential of the genotype, requiring the choice of more adapted and stable genotypes in order to take advantage of information on the interaction, justifying the application of statistical analyzes of adaptability and stability (Souza et al, 2018).…”
Section: Resultsmentioning
confidence: 99%